DISASTER MANAGEMENT-ROLE OF FORENSIC EXPERT (Indian Internet Journal of Forensic Medicine and Toxicology, 2004)
Disasters have existed ever since the existence of the mankind. The ‘Hindu Philosophy’ and ‘Greek’ philosopher Empedocles  presumed that Universe consists of five elements: Earth, Fire, Air, Sun, and Water, from there comes the manifestation of violence like Earthquakes, Volcanoes, Cyclones, and Floods. The focus of nature has been relentlessly violent and Natural Disasters have been called the greatest destroyer of lives and property (Australian Counter Disaster College, 1984).  With the development of Chemical Processes and Manufacturing Industry, “Nuclear Bomb Explosion” in 1945, “Bhopal Gas Tragedy” in India on 3rd December 1984, and “Terrorist Attack on World Trade Center” in USA on 9/11th September 2001, and continuing technological advances, it is inevitable that Biological and Chemical Disasters are just round the corner and community must prepare themselves for these disasters. The growing “Terrorism” in the World over has added to ever increasing list and severity of Man Made Disasters.
Keywords: Calamities; Disaster; Management; Man Made; Natural